Synthesis and magnetic properties of the chromium-doped iron sulfide Fe1−xCrxS single crystalline nanoplates with a NiAs crystal structure. Issue 24 (28th June 2015) - Starchikov, S. S.; Lyubutin, I. S.; Lin, Chun-Rong; Tseng, Yaw-Teng; Funtov, K. O.; Ogarkova, Yu. L.; Dmitrieva, T. V.; Ivanova, A. G.
<x xml:space="preserve">Abstract</x> Chromium-doped pyrrhotite Fe1−xCrxS nanoparticles have been synthesized. The specific magnetic properties important for applications in technical devices can be tuned by chromium doping.